2021
DOI: 10.1038/s41386-021-01188-y
|View full text |Cite
|
Sign up to set email alerts
|

The prediction-error hypothesis of schizophrenia: new data point to circuit-specific changes in dopamine activity

Abstract: Schizophrenia is a severe psychiatric disorder affecting 21 million people worldwide. People with schizophrenia suffer from symptoms including psychosis and delusions, apathy, anhedonia, and cognitive deficits. Strikingly, schizophrenia is characterised by a learning paradox involving difficulties learning from rewarding events, whilst simultaneously ‘overlearning’ about irrelevant or neutral information. While dysfunction in dopaminergic signalling has long been linked to the pathophysiology of schizophrenia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 262 publications
(391 reference statements)
0
30
0
Order By: Relevance
“…This adds to a growing body of evidence supporting the potential for variation in LI performance to represent a surrogate marker to detect the core psychological disturbance that increases the risk for conversion to a full-blown psychotic disorder (Granger et al, 2020). It has been suggested that mesolimbic dopaminergic hyperfunction drives maladaptive associative learning across the early trajectory of the illness ( Kätzel et al, 2020 ; Millard et al, 2021 ), with the limited efficacy of antipsychotics, which act via D2 receptor blockade, relating to insufficient targeting to reverse aberrant salience processing and the psychological impact of years of maladaptive associate learning processes ( Kätzel et al, 2020 ). This hypothesis and supporting data highlight the potential for early intervention that would be tailored to modification of the mechanisms of salience allocation.…”
Section: Discussionmentioning
confidence: 99%
“…This adds to a growing body of evidence supporting the potential for variation in LI performance to represent a surrogate marker to detect the core psychological disturbance that increases the risk for conversion to a full-blown psychotic disorder (Granger et al, 2020). It has been suggested that mesolimbic dopaminergic hyperfunction drives maladaptive associative learning across the early trajectory of the illness ( Kätzel et al, 2020 ; Millard et al, 2021 ), with the limited efficacy of antipsychotics, which act via D2 receptor blockade, relating to insufficient targeting to reverse aberrant salience processing and the psychological impact of years of maladaptive associate learning processes ( Kätzel et al, 2020 ). This hypothesis and supporting data highlight the potential for early intervention that would be tailored to modification of the mechanisms of salience allocation.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that both aspects of PRT performance correlated with the P50 ratio and were modulated by smoking in similar ways supports the notion that rather than being pathophysiologically distinct processes, these processes likely overlap to some extent in terms of their underlying mechanisms. Predictive coding theories [ 1 ] and recent integrative models of psychosis emanating from these theories [ 2 , 3 ] provide us with a possible explanation for this link. Predictive coding theory suggests that reward learning and sensory gating are both critically reliant on more general aspects of prediction and prediction error, with recent neurobiological frameworks positioning phasic striatal dopamine firing as the key aberration-driving deficits in prediction error signaling in psychosis [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Predictive coding theories [ 1 ] and recent integrative models of psychosis emanating from these theories [ 2 , 3 ] provide us with a possible explanation for this link. Predictive coding theory suggests that reward learning and sensory gating are both critically reliant on more general aspects of prediction and prediction error, with recent neurobiological frameworks positioning phasic striatal dopamine firing as the key aberration-driving deficits in prediction error signaling in psychosis [ 2 , 3 ]. This has important implications for how we understand the disparate symptoms of psychosis, like anhedonia and auditory hallucinations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations